2003
DOI: 10.1063/1.1623480
|View full text |Cite
|
Sign up to set email alerts
|

Absolute yields of CO(a′ 3Σ+, d 3Δi,e 3Σ−)+O from the dissociative recombination of CO2+ ions with electrons

Abstract: Articles you may be interested in Dissociative recombination of H + ( H 2 O ) 3 and D + ( D 2 O ) 3 water cluster ions with electrons: Cross sections and branching ratiosThe flowing afterglow technique has been applied to the dissociative recombination CO 2 ϩ ϩe Ϫ →CO*ϩO, in order to determine the radiative cascade contribution from high-energy triplet states of CO, (aЈ 3 ⌺ ϩ ), (d 3 ⌬ i ), and (e 3 ⌺ Ϫ ), to the total yield of the long-lived (a 3 ⌸) state. The yields of the aЈ, d, e states were found to be ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…To evaluate the contribution of this source, we use the results from the study by Fox [2004] where the densities of CO 2 + and electrons were calculated for low solar activity. Using these values of densities, the electron temperature adopted by Hanson et al [1977], the rate coefficient of Seiersen et al [2003], and the recent measurements of branching ratios of dissociative recombination of CO 2 + into the a 3 Π state (equal to 0.18 according to Skrzypkowski et al [1998] and Rosati et al [2003]), the contribution of the CO 2 + dissociative recombination can be evaluated. This production rate is shown in Figure 4 (middle).…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the contribution of this source, we use the results from the study by Fox [2004] where the densities of CO 2 + and electrons were calculated for low solar activity. Using these values of densities, the electron temperature adopted by Hanson et al [1977], the rate coefficient of Seiersen et al [2003], and the recent measurements of branching ratios of dissociative recombination of CO 2 + into the a 3 Π state (equal to 0.18 according to Skrzypkowski et al [1998] and Rosati et al [2003]), the contribution of the CO 2 + dissociative recombination can be evaluated. This production rate is shown in Figure 4 (middle).…”
Section: Resultsmentioning
confidence: 99%
“…Later data (Tsuji et al, 1995) showed a very small population in v ¼ 2, the highest level detected, consistent with this. However, it would be surprising if this were also the case for the CO(a 03 S þ ) data, since the authors (Rosati et al, 2003) are well aware of this potential problem. The populations for the CO(d 3 D i ) are however quite consistent between the two recent sets of data.…”
Section: Internal Excitation Of Recombination Productsmentioning
confidence: 99%
“…Vibrational state populations of electronically excited states generated in the electron dissociative recombination of CO þ 2 , HCO þ and N 2 H þ . a: For CO þ 2 , comparisons of data sets are given: CO(A 1 Q ) a (Tsuji et al, 1995) b (Gutcheck and Zipf, 1973), dotted lines; CO(d 3 D I ) g (Tsuji et al, 1998) d (Rosati et al, 2003), solid lines; CO(a 03 S þ ) e (Rosati et al, 2003) f (Tsuji et al, 1998), dashed lines. b: For all data.…”
Section: A Quantum Nature Of Recombinationmentioning
confidence: 99%
“…Rate coefficients for ionneutral reactions are taken from Fox and Sung (2001). Recently, Seiersen et al (2003) have measured recombination rates for the e-CO + 2 collision, with yield of 0.87 for the channel producing CO of which CO(a 3 Π) production yield is 0.29 (Skrzypkowski et al, 1998;Rosati et al, 2003). Ion and electron temperatures are taken from Fox (2009).…”
Section: Modelmentioning
confidence: 99%